Creano Cafe / Nabilah Perman... [et al.] - Jumat, Khalidamona; H James Arab, Ivy Sendralisa; Mohd Sohaimi, Sri Shaliza Sharmie; Duraman, Syariah Izzati; Felex, Mira Emelyta; Perman, Nabilah (2015)
CREANO Cooperation is a company that created to sell a creative and innovative product. CREANO Cafe is one of the dessert cafe that serves various types of cakes located at Kota Kinabalu, Sabah,Malaysia. This name symbolizing that our cafe focus on selling our main product which is Creano Snack that is based on creativity and innovation of desserts and cakes that may attract all sweet lovers. This business is a partnership business consists of 6 contributors. We are targeting to expand our business throughout the world in long term achievement.